How do you find all the zeros of (3x^6+x^2-4)(x^3+6x+7)(3x6+x24)(x3+6x+7)?

1 Answer
Jul 16, 2016

This product has zeros:

  • 11

  • -11 (with multiplicity 22)

  • +-(sqrt((4sqrt(3)-3)/12))+-(sqrt((4sqrt(3)+3)/12))i±43312±43+312i

  • 1/2+-(3sqrt(3))/2 i12±332i

Explanation:

The zeros of (3x^6+x^2-4)(x^3+6x+7)(3x6+x24)(x3+6x+7) are all the values of xx which are zeros of (3x^6+x^2-4)(3x6+x24) or (x^3+6x+7)(x3+6x+7).

color(white)()
Zeros of bb(3x^6+x^2-4)

Note that all of the degrees are even and the sum of the coefficients is 0.

Hence this sextic has zeros +-1 and quadratic factor:

(x-1)(x+1) = x^2-1

We find:

3x^6+x^2-4 = (x^2-1)(3x^4+3x^2+4)

Treating the remaining quartic factor as a quadratic in x^2 and using the quadratic formula, we find:

x^2 = (-3+-sqrt(3^2-4(3)(4)))/(2*3)

=(-3+-sqrt(9-48))/6

=(-3+-sqrt(-39))/6

=-1/2+-sqrt(39)/6i

The square roots of a+-bi are:

+-(sqrt((sqrt(a^2+b^2)+a)/2)) +- (sqrt((sqrt(a^2+b^2)-a)/2))i

(see https://socratic.org/s/aw38evei)

So, putting a=-1/2 and b=sqrt(39)/6 we find:

a^2+b^2 = (-1/2)^2+(sqrt(39)/6)^2 = 1/4+39/36 = 48/36 = 4/3

So:

sqrt(a^2+b^2) = sqrt(4/3) = sqrt(4/9*3) = (2sqrt(3))/3

Hence:

x = +-(sqrt(((2sqrt(3))/3-1/2)/2))+-(sqrt(((2sqrt(3))/3+1/2)/2))i

=+-(sqrt((4sqrt(3)-3)/12))+-(sqrt((4sqrt(3)+3)/12))i

color(white)()
Zeros of bb(x^3+6x+7)

Notice that -1 is a zero, so (x+1) is a factor and we find:

x^3+6x+7 = (x+1)(x^2-x+7)

The remaining quadratic factor has zeros given by the quadratic formula:

x = (1+-sqrt((-1)^2-4(1)(7)))/(2*1)

=(1+-sqrt(-27))/2

=1/2+-(3sqrt(3))/2 i